2020
DOI: 10.1038/s41598-020-67019-0
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Performance of Body Composition Parameters in Prediction of Death in Hospitalized Patients on Maintenance Hemodialysis: A Cohort Study

Abstract: We compared the prognostic value of nutritional or volumetric parameters measured by body composition in hospitalized patients on maintenance hemodialysis. We conducted a cohort study to assess the association of different parameters of body composition with all-cause mortality in inpatients admitted to our nephrology department from January 2014 to December 2016. Of the 704 study patients, 160 (22.7%) died during a median follow-up of 33 months. In multivariate adjusted Cox models, higher ratio of extracellul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 43 publications
0
4
0
Order By: Relevance
“…Extracellular mass is mainly comprised of extracellular fluid. It has been suggested in previous studies that the ECW/BCM performed better than the OH/ECW as well as the ratio of ECW to intracellular water (ECW/ICW) in the assessment of fluid status [ 7 , 8 ]. Higher ECW/ICW ratios are associated with functional disability levels in patients with knee osteoarthritis [ 18 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Extracellular mass is mainly comprised of extracellular fluid. It has been suggested in previous studies that the ECW/BCM performed better than the OH/ECW as well as the ratio of ECW to intracellular water (ECW/ICW) in the assessment of fluid status [ 7 , 8 ]. Higher ECW/ICW ratios are associated with functional disability levels in patients with knee osteoarthritis [ 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have suggested the ECW/BCM as a potential predictive factor for mortality risk in HD patients [ 6 ]. The ECW/BCM was found to perform better than overhydration and extracellular water (OH/ECW) in the assessment of fluid status in patients with acute kidney injury who required renal replacement therapy [ 7 ] as well as in those undergoing maintenance hemodialysis (MHD) [ 8 ]. Unfortunately, little is known about the relationship between the whole-body ECW/BCM ratio before dialysis and functional capabilities in MHD patients.…”
Section: Introductionmentioning
confidence: 99%
“…With the 3C BIS method, estimation of body composition is based on a theoretical approach without the use of populationspecific regression equations. Lean tissue index (LTI), which corresponds to LTM, divided by height 2 , below the 10th percentile of a healthy age-matched reference population was independently related to outcome in most, but not all studies (8,15,37,38). Still, in a meta-analysis including over 15,000 patients, a low LTI was associated with increased mortality [Hazard ratio 1.53 (95% CI: 1.41-1.64)] (39).…”
Section: Bioelectrical Impedancementioning
confidence: 99%
“…Values of FFM, BFM, skeletal muscle mass (SMM), body cell mass (BCM), total body water (TBW), extracellular water (ECW) were extracted from the device. Fat-free mass index (FFMI), fat mass index (FMI) 16,17) , skeletal muscle index (SMI) 18) , body cell mass index (BCMI) 19,20) were calculated respectively as FFM, FM, SMM, and SCM divided by the squared height. ECW/TBW 21) is the ECW divided by TBW.…”
Section: Body Compositionmentioning
confidence: 99%